Hardness and Electrical Resistivity of Al-13 wt % Mg2Si Pseudoeutectic Alloy - Kaygisiz, Yusuf; Marasli, Necmettin (PLEIADES PUBLISHING INC, 2017)
In the present work, effect of growth rates on microhardness, electrical properties and microstructure for directionally solidified Al-13 wt % Mg2Si pseudoeutectic alloy at a constant temperature gradient were studied. Directional solidification process were carried out with five different growth rates (V = 8.33-175.0 mu m/s) at a constant temperature gradient (G = 6.68 K/mm) by using a Bridgman type directional solidification furnace. Microstructure of directionally solidified Al-13 wt % Mg2Si pseudoeutectic alloy was observed as Mg2Si coral-like structure phase dispersed into primary alpha-Al phase matrix. The electrical resistivity for Al-13 wt % Mg2Si pseudoeutectic alloy, were measured by the d. c. four-point probe method. The dependency of microhardness and electrical resistivity on growth rates were obtained as IIV = 135.7 (V)(0.09) and rho = 17.30 x 10(-8)(V)(0.08) respectively for Al-Mg2Si pseudoeutectic alloy. The results obtained in present work were compared with the previous similar experimental results.
Keywords: directional solidification; pseudoeutectic alloy; aluminum alloy; microhardness; electrical properties; GROWTH-RATE; MICROSTRUCTURE; SOLIDIFICATION; Metallurgy & Metallurgical Engineering